Ethnic Identity, Social Class and Consumption Pattern Among Three Major Ethnic Groups in Nigeria - Owolabi, Ademola Benjamin (Advances in Social Sciences Research Journal, 2014)
Consumers from different ethnic group and social class are known to vary dramatically in how they spend their income. In this study we aim to shed light on how ethnic identity and social class affect consumption pattern of the three major ethnic groups in Nigeria. A total of 398 participants drawn from three states across the country took part in the study. Three standardize instruments were used to collect data. Three hypotheses were tested. Results reveal partial significant effect of ethnic identity, ethnic group and social class on consumption pattern.